USING COST-VOLUME-PROFIT TO ANALYSE THE VIABILITY OF IMPLEMENTING A NEW DISTRIBUTION CENTER - Etges, Ana Paula Beck da Silva; Calegari, Rafael; Rhoden, Marisa Ignez dos Santos; Cortimiglia, Marcelo Nogueira (Brazilian Journal of Operations & Production Management, 2016)
Firms are constantly improving their activities in order to become more competitive. With the diffusion of international competition and easier access to global markets, effective logistic and inventory management strategies become essential to all players. In this sense, there is a clear tradeoff between inventory costs and service level. A common strategy to address this issue is to locate distribution centers (DC) near key markets. However, the decision to build new DCs must be supported by clear and convincing analysis. In this context, this paper reports the use of cost-volume-profit analysis to assess the viability of establishing a new DC by a real company that manufactures radiopharmaceutical products. The researchers collected and analysed detailed financial information from the company and compared the current scenario with potential future scenarios using the cost-volume-profit technique. Next, expected firm profitability is compared for two scenarios: with and without the new DC.